2017
DOI: 10.1246/cl.170853
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Enantioselective Rh- or Ir-catalyzed Directed C(sp3)–H Borylation with Phosphoramidite Chiral Ligands

Abstract: Enantioselective heteroatom-directed C(sp 3 )H borylation reactions of 2-aminopyridines and 2-alkylpyridines with Rh-and Ir catalytic systems using commercially available chiral monophosphine ligands, respectively, were developed. This methodology provides an innovative example of a homogeneous catalytic system for C(sp 3 )H borylation, and allows the direct synthesis of optically active alkylboronates with a moderate level of enantioselectivity. Keywords: C-H activation | Borylation | Asymmetric catalysisThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Rh‐ and Ir‐catalyzed asymmetric C—H borylation has emerged as a viable approach to access optically active organoboron compounds in an atom‐ and step‐economic way under mild reaction conditions. [ 18 ] However, it is still subjected to limitations such as the reaction types. Recently, we reported the amide‐directed Ir‐catalyzed enantioselective C(sp 3 )–H borylation of cyclopropanes using chiral bidentate boryl ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Rh‐ and Ir‐catalyzed asymmetric C—H borylation has emerged as a viable approach to access optically active organoboron compounds in an atom‐ and step‐economic way under mild reaction conditions. [ 18 ] However, it is still subjected to limitations such as the reaction types. Recently, we reported the amide‐directed Ir‐catalyzed enantioselective C(sp 3 )–H borylation of cyclopropanes using chiral bidentate boryl ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Following the reported heteroatom-directed borylation of C(sp 3 )-H bonds with Rh-and Ircatalyst systems based on heterogeneous immobilized silica-supported bridgehead monophosphine, Silica-SMAP and Silica-TRIP, by Sawamura and co-workers (see Figures 42-46) several homogeneous monophosphines were observed to also promote the challenging C(sp 3 )-H borylation. For example, the borylation of 2-aminopyridine derivatives with bis(pinacolatodiboron) under rhodium catalysis gave the corresponding secondary -aminoboronate with the sterically hindered P(o-tol)3 and P(tBu)3 identified to be the most effective ligands (Reyes, Harada, et al, 2017). These results open a synthetic opportunity to extend the reaction protocol to a catalytic asymmetric technique to directly synthesize enantioenriched alkylboronates from functionalized alkanes.…”
Section: Asymmetric Borylation Of C(sp 3 )-H Bondsmentioning
confidence: 94%
“…The asymmetric discrimination of unactivated enantiotopic methylene C—H bonds is a long‐standing challenge in organic synthesis. In 2017, Sawamura group reported that the chiral monophosphoramidite ligands could promote the borylation of methylene C(sp 3 )—H bonds with moderate enantioselectivities . After an extensive optimization of the catalysts, they disclosed an iridium‐catalyzed asymmetric borylation of unactivated methylene C(sp 3 )—H bonds in 2‐alkylpyridines and 2‐alkylazole derivatives by using the 1,1'‐Bi‐2‐naphthol (BINOL)‐based chiral monophosphite ligand L1 (Scheme ) .…”
Section: Recent Advancesmentioning
confidence: 99%